2021
DOI: 10.1186/s12889-021-11918-y
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent sick leave after COVID-19: investigating the first wave of the pandemic in a comprehensive Swedish registry-based study

Abstract: Background Sick-leave due to COVID-19 vary in length and might lead to re-current episodes. The aim was to investigate recurrent sick leave due to COVID-19 during the first wave. Methods This is a registry-based cohort study. The study comprises all people with sickness benefit due to COVID-19 in Sweden in March 1–August 31, 2020. Data from the Swedish Social Insurance Agency, the Swedish National Board of Health and Welfare, and Statistics Sweden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Others have pointed to interactions between age and sex, e.g., less sick leave in infected females ages 20–44 compared to infected females ages 45–70 years 19 . Additionally, a Swedish registry-based cohort study reported that people with recurrent sick leave were older, more often female, and more likely to have been on sick leave prior to the pandemic 14 . In our study, we observed that the RD for substantial sick leave between SARS-CoV-2 test-positives and -negatives was greater for females (RD 3.9, 95% CI 3.6–4.2) than for males (RD 2.1, 95% CI 1.8–2.5), and that females as well as persons 50–65 years had a slightly higher prevalence of sick leave compared to the general population, irrespective of test status.…”
Section: Discussionmentioning
confidence: 99%
“…Others have pointed to interactions between age and sex, e.g., less sick leave in infected females ages 20–44 compared to infected females ages 45–70 years 19 . Additionally, a Swedish registry-based cohort study reported that people with recurrent sick leave were older, more often female, and more likely to have been on sick leave prior to the pandemic 14 . In our study, we observed that the RD for substantial sick leave between SARS-CoV-2 test-positives and -negatives was greater for females (RD 3.9, 95% CI 3.6–4.2) than for males (RD 2.1, 95% CI 1.8–2.5), and that females as well as persons 50–65 years had a slightly higher prevalence of sick leave compared to the general population, irrespective of test status.…”
Section: Discussionmentioning
confidence: 99%
“…Because the HCS globally already struggles with thousands of vacancies, it is imperative to identify the factors resulting in staff SAs and to take steps to prevent morbidity and mortality among the staff responding to the COVID-19 pandemic [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 46.3% of women and 31.1% of men in the sub-acute phase, and 35.6% of women and 29.9% of men in the post COVID-19 phase reported disability of varying degrees for the WHODAS item “Working ability.” These proportions are in comparison with the 25.7% of women and 25.8% of men among controls who reported disability, and a possible need for rehabilitation and recovery to regain their ability to work. In the Swedish population, risk factors for recurrent sick leave owing to COVID-19 have been found to be female sex, prior sick leave, older age [ 23 ], and the severity of COVID-19 [ 24 ]. The large predominance of women (85.8%) in the present study could be explained by the sex difference in Swedish public employees (71.3% women) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%